A Commentary on Autism and Moral Development: What Can We Learn from the Sandy Hook School Shooting? - Hartley-McAndrew, MD, FAAP, Michelle; Crawford, PhD, Donald (North American Journal of Medicine and Science, 2013)
The Sandy Hook Elementary School shooting has left many people wondering whether the shooter’s diagnosis along the autism spectrum is what caused the unthinkable crime that transpired. This commentary explores moral development in both the typical and autism populations. It reviews previous studies done on the autism population regarding their understanding of right and wrong actions even when they lack theory of mind. A lack of empathy is often attributed to individuals with autism spectrum disorders, but many studies show that while they may fail to articulate another person’s point of view, they are not completely unresponsive to the distress or moral dilemmas of others. This commentary aims to dispel any misunderstanding that autism spectrum disorder equals lack of empathy, which leads to violence. It also hopes to alert the medical community treating those with autism spectrum disorders that the diagnosis of the patient may not end at autism alone. Thus other personality disorders may be present requiring intensive treatment and referral. [N A J Med Sci. 2013;6(3):163-166. DOI: 10.7156/najms.2013.0603163]